2014
DOI: 10.1210/jc.2013-3629
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sleep Duration, Daytime Nap Duration, and Osteoporosis Vary by Sex, Menopause, and Sleep Quality

Abstract: Sleep durations of 7-8 h/d, 9-10 h/d, and 10 h/d or longer, as well as longer daytime napping times, tend to present higher risks of having osteoporosis, and this tendency is most obvious in postmenopausal women reporting good-quality sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 35 publications
9
67
3
3
Order By: Relevance
“…With respect to sleep duration, participants in the control group averaged 6-7 hours of sleep per night and < 6 hours, but osteoporosis patients fell into two ranges, <6 hours or >7 hours. A previous study demonstrated that a long sleep duration may increase the risk for osteoporosis [23]. Our outcomes showed that more individuals in the osteoporosis group slept for longer periods of time (>7 h) compared with those in the control group.…”
Section: Discussionsupporting
confidence: 44%
“…With respect to sleep duration, participants in the control group averaged 6-7 hours of sleep per night and < 6 hours, but osteoporosis patients fell into two ranges, <6 hours or >7 hours. A previous study demonstrated that a long sleep duration may increase the risk for osteoporosis [23]. Our outcomes showed that more individuals in the osteoporosis group slept for longer periods of time (>7 h) compared with those in the control group.…”
Section: Discussionsupporting
confidence: 44%
“…Another Chinese study found an association between sleep duration of 9 h or longer per day and a higher risk of osteoporosis in postmenopausal women, but not in men [17]. In addition, a prospective cohort study of 8101 women aged 69 years or older observed that women with self-reported sleep duration of 10 h or longer per day had a significantly higher risk of non-spinal fracture [21].…”
Section: Discussionmentioning
confidence: 98%
“…However, the conclusions remain inconsistent. Some studies observed a positive association between long sleep duration and the risk of osteoporosis [4,17], while Fu and his colleagues suggested short sleep duration was associated with lower bone mineral density [18]. Small sample sizes, different exposure distributions, and other characteristics of the study populations may potentially explain the inconsistency in these findings.…”
Section: Introductionmentioning
confidence: 99%
“…In the primary studies done between 2006-2012, criteria to define OS were self-reported; and when assessed by DXA analysis, only two authors 11,30 made assessments of Tscore that allowed distinction between OP and OS. Moreover, the authors considered large populations from middle-aged to older subjects more frequently in women, with definition of sleep duration and sleep quality based on just one question, "how many hours you sleep," without specific assessment by a validated questionnaire.…”
Section: Discussionmentioning
confidence: 99%